Realistic planning of research and development projects - Kuchta, Dorota (Business, Management and Economics Engineering, 2019)
Purpose – the purpose of the article is to propose a more flexible approach to the planning of research and development projects, especially for the needs of project calls. In those calls, financial means are often refused to projects with a high level of uncertainty. The proposal should support a positive assessment of the most pathbreaking projects and a flexible reaction to the failure or partial failure of such projects. Research methodology – In the proposal type 1 and type 2 fuzzy sets are applied. The proposal will is using case studies. Findings – the results will modify the way research and development project are planned and controlled. Research limitations – the proposal has not been verified in practice, for which many more case studies and cooperation with financing institutions would be necessary. Also, it does not use up all the modelling possibilities of uncertainty and dependencies between various uncertain elements of the project plan. Practical implications – the results might be used in the design of forms used by various financing institutions (e.g. European Commission or national research funding institutions) in project calls. Originality/Value – the proposal presents an entirely different way research and development projects should be planned and described. Type 2 fuzzy sets are used for the description, where various elements of the project plan (e.g. objectives, methods, tasks) are assigned a possibility degree (of attainment, of usage etc.).